Yield, pomological characteristics, bioactive compounds and antioxidant activity of Annona cherimola Mill. grown in mediterranean climate - Stefano Puccio; Anna Perrone; Giuseppe Sortino; Giuseppe Gianguzzi; Carla Gentile; Vittorio Farina (AIMS Agriculture and Food, 2019)
The agronomic and qualitative responses of the cherimoya (Annona cherimola Mill.) fruit grown in Mediterranean climate are not properly studied. Fruits of Fino de Jete, the most diffused worldwide cultivar of cherimoya, and Torre 1 a new genotype obtained by breeding program in Sicily, Italy, were collected at commercial ripening and subjected to productive (yield efficiency, number of fruits, crop load), analytical (fruit weight, transversal diameter, longitudinal diameter, total soluble solid content, titratable acidity, seed weight, seed number, peel and pulp weight, pulp/seed ratio and colorimetric analysis), bioactive compound content (total antioxidant activity, Phenolic and Carotenoid) and sensory evaluations by a semi-trained panel, recorded over two productive seasons. Even if the climatic conditions prevailing in Sicily differ from those of most cherimoya-growing regions, the two observed cultivars generally showed yields and fruit qualitative characteristics comparable with those harvested in other Mediterranean and Tropical areas. Fino de Jete confirmed its quality standard thanks to its yields performance and fruit weight. Despite of this, Torre 1 showed interesting physico-chemical, sensory properties and bioactive compounds, suitable for the consumer needs: less number of seeds and better pulp/seed ratio, better total solid soluble content/tritratable acidity ratio, higher phenolic content and antioxidant activity. These results suggest that cherimoya can be cropped for fresh production in Mediterranean environment with promising yields and good standards of fruit quality.